Perlindungan Hukum Pemegang Saham Perseroan Terbatas Terbuka Pada Rapat Umum Pemegang Saham Secara Elektronik - Sutiono, Marvel Romi; Sajogo, Kenneth Bradley (Acten Journal Law Review, 2024)
The organs of a Limited Liability Company are the GMS, Board of Directors, and Commissioners, each of which has its own function. Under normal conditions, the GMS of a Public Limited Company is carried out conventionally with a direct meeting, but now it is carried out electronically based on POJK 16/2020. The electronic GMS regulations have been regulated in Article 77 of the Limited Liability Company Law, which requires the signatures of all GMS participants on the minutes, while Article 12 of POJK 16/2020 stipulates that it does not require the signatures of GMS participants and must be made with a notary deed. This study uses a normative legal research type using a statutory approach, a conceptual approach, and a historical approach. The conclusions of the discussion are as follows. First, the meaning of the electronic GMS of a Public Limited Company is part of a public limited company that is born from a group of shareholders and has its own authority and its implementation using electronic media. GMS which used to be conventional can now be carried out using electronic media. Second, the nature of electronic signing of the minutes of the GMS of Public Limited Companies in Article 12 of POJK 16/2020 has not provided legal protection for shareholders and there is disharmony with Article 77 paragraph (4) of the Limited Liability Company Law and the Notary Law. The minutes of the GMS of a Limited Liability Company are a form of internal legal protection and laws and regulations are external legal protection. Keywords: Shareholders; GMS; Electronic; Legal Protection